Charakterystyka funkcjonujących na polskim rynku ubezpieczeń następstw nieszczęśliwych wypadków - Jędrzychowska, Anna (Wydawnictwo Akademii Ekonomicznej im. Oskara Langego we Wrocławiu, 2005)
The article shows the collision insurance as a product of insurance market. It consists of a brief description of the collision and function of insurance construction. The main part of the article concentrates on the way the product functions on the Polish market, the author of the article argues in respect for the value of the premiums which enter the insurance market they are of lesser importance, but in respect for the number of signed contracts, this kind of premiums are bought the most often by Poles. (original abstract)
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2005; nr 1088, t. 1, s. 231-241